Green Synthesis, Characterization, Antimicrobial, Anti-Cancer, and Optimization of Colorimetric Sensing of Hydrogen Peroxide of Algae Extract Capped Silver Nanoparticles - Abdelaziz Elgamouz; Hamid Idriss; Chahlaa Nassab; Alaa Bihi; Khalid Bajou; Kamrul Hasan; Mohammad Abu Haija; Shashikant P. Patole (Nanomaterials, 2020)
A green and cost-effective technique for the preparation of silver nanoparticles (Algae-AgNPs) as a colorimetric sensor for hydrogen peroxide (H2O2) is described. Silver nanoparticles were capped using the green algae (Noctiluca scintillans) extract at an optimum time of 3 h at 80 °C. The pH of the plant extract (pH = 7.0) yields nanoparticles with a mean size of 4.13 nm and a zeta potential of 0.200 ± 0.02 mV and negative polarity, using dynamic light scattering (DLS). High-resolution transmission electron microscopy (HRTEM) analysis showed regular spherical particles with the average size of 4.5 nm. Selected area electron diffraction (SAED) results revealed the polycrystalline nature of the silver nanoparticles. The obtained patterns were indexed as (111), (200), (220), and (311) reflections of the fcc (face centered cubic) silver crystal based on their d-spacing of 2.47, 2.13, 1.49, and 1.27 Å, respectively. The apparent color change from brown to colorless was observed when nanoparticles reacted with H2O2. Linear responses were obtained in three different ranges (nM, µM, and mM). Limits of detection (LOD) of 1.33 ± 0.02 and 1.77 ± 0.02 nM and quantitation limits (LOQ) of 7.31 ± 0.03 and 9.67 ± 0.03 nM were obtained for Abs and ΔAbs calibration curves, respectively. 10% v/v Algae-AgNPs solution inhibited Staphylococcus aureus over Escherichia coli, while a 50% reduction of tumor cell growth of MDA-MB-231 human breast adenocarcinoma was obtained.